Bletilla striata Polysaccharide Promotes Diabetic Wound Healing Through Inhibition of the NLRP3 Inflammasome - Yan Zhao; Yan Zhao; Qibin Wang; Shan Yan; Shan Yan; Jun Zhou; Jun Zhou; Liangyong Huang; Haitao Zhu; Fang Ye; Yonghong Zhang; Lin Chen; et al. (Frontiers Media S.A., 2021)
The aim of this study was to evaluate the therapeutic effects of Bletilla striata polysaccharide (BSP) on wound healing in diabetes mellitus (DM) and to explore the underlying mechanisms. DM mouse models were induced by high fat-diet feeding combined with low-dose streptozocin injection. To establish diabetic foot ulcer (DFU) models, DM mice were wounded on the dorsal surface. Subsequently, mice were treated with vehicle or BSP for 12 days and wound healing was monitored. The effects of BSP on the production of interleukin-1β (IL-1β), tumor necrosis factor-α, macrophages infiltration, angiogenesis, the activation of nucleotide-binding and oligomerization (NACHT) domain, leucine-rich repeat (LRR), and pyrin domain (PYD)-containing protein 3 (NLRP3) inflammasome, and insulin sensitivity in wound tissues were subsequently evaluated. Separated- and cultured- bone marrow-derived macrophages (BMDMs) and cardiac microvascular endothelial cells (CMECs) were isolated from mice and used to investigate the effects of BSP on cell viability, reactive oxygen species (ROS) generation, NLRP3 inflammasome activation and insulin sensitivity in vitro following exposure to high glucose (HG). BSP administration accelerated diabetic wound healing, suppressed macrophage infiltration, promoted angiogenesis, suppressed NLRP3 inflammasome activation, decreased IL-1β secretion, and improved insulin sensitivity in wound tissues in DM mice. In vitro, co-treatment with BSP protected against HG-induced ROS generation, NLRP3 inflammasome activation, and IL-1β secretion in BMDMs, and improved cell viability and decreased ROS levels in CMECs. Moreover, in HG exposed BMDMs-CMECs cultures, BSP treatment suppressed NLRP3 inflammasome activation and IL-1β secretion in BMDMs, and improved cell viability and insulin sensitivity in CMECs. Furthermore, treatment with IL-1β almost completely suppressed the beneficial effects of BSP on the NLRP3 inflammasome, IL-1β secretion, and insulin sensitivity in HG-treated BMDMs-CMECs. BSP promotes DFU healing through inhibition of the HG-activated NLRP3 inflammasome.